1978
DOI: 10.1136/jcp.31.11.1091
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the use of artificial substrates for the diagnosis of Gaucher's disease.

Abstract: A patient with Gaucher's disease is described, in whom the disease could not be diagnosed enzymically in liver and leucocytes using artificial substrate 4-methylumbelliferyl beta-glucoside. Normal activity was found in the liver, and about 60% of control activity was determined in the patient's leucocytes. In contrast, when [14C]-N-stearoyl glucocerebroside was employed as a substrate, activity as low as 5% of control has been found in all the proband's tissues, and carrier levels were determined in the proban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Fluorescence-based GBA Activity Assays-The activity of cellular GBAs was analyzed using 4-methylumbelliferyl-␤-D-glucopyranoside (4-MU-␤-D-glucopyranoside) (Sigma) (26,27) as a fluorescent substrate. Cleavage of 4-MU-␤-D-glucopyranoside was monitored in real time in a Fluostar Omega reader (BMG Labtech) at 29°C using the filter pair 355 nm/460 nm for excitation and emission, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence-based GBA Activity Assays-The activity of cellular GBAs was analyzed using 4-methylumbelliferyl-␤-D-glucopyranoside (4-MU-␤-D-glucopyranoside) (Sigma) (26,27) as a fluorescent substrate. Cleavage of 4-MU-␤-D-glucopyranoside was monitored in real time in a Fluostar Omega reader (BMG Labtech) at 29°C using the filter pair 355 nm/460 nm for excitation and emission, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although these fluorogenic substrates are sensitive in the assay and easy to use, they may not reflect physiological conditions in cells. In addition, the specificity of fluorogenic substrates could be a problem in assays using cell or tissue preparations instead of purified recombinant enzymes, as they may be cleaved by other cellular enzymes present in these crude preparations [16–18]. Alternatively, the natural substrate, glucosylceramide, can be used in the glucocerebrosidase assay to more accurately measure glucocerebrosidase activity in enzyme preparations from cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the various fluorometric diagnostic assays give ambiguous results when liver is the source of the enzyme [3,9]. The problem with using a fluorometric assay is that liver is a particularly rich source of the non-specific P-glucosidase.…”
Section: Introductionmentioning
confidence: 99%